Echinocandins as alternative treatment for HIV-infected patients with Pneumocystis pneumonia. (1st July 2019) - Huang, Yu-Shan; Liu, Chun-Eng; Lin, Shih-Ping; Lee, Chen-Hsiang; Yang, Chia-Jui; Lin, Chi-Ying; Tang, Hung-Jen; Lee, Yi-Chien; Lin, Yi-Chun; Lee, Yuan-Ti; Sun, Hsin-Yun; Hung, Chien-Ching
Abstract : Objectives: Treatment with trimethoprim-sulfamethoxazole for Pneumocystis pneumonia (PCP) is often associated with adverse effects. Echinocandins, by inhibiting the cyst form of Pneumocystis jirovecii, may be an alternative therapy for PCP. However, clinical experience with echinocandins in the treatment of PCP remains limited among HIV-infected patients. Methods: From August 2013 to April 2018, data of HIV-infected patients with confirmed PCP who received echinocandins as alternative treatment because of intolerance or unresponsiveness to trimethoprim-sulfamethoxazole were retrospectively reviewed to assess the effectiveness and safety of echinocandins alone or in combination with other agents. Results: In total, 34 patients were included, with a median CD4 + count of 27 cells/μl [interquartile range (IQR), 20–93). Twenty-four patients (70.6%) presented with moderate-to-severe PCP. The most common adverse effects leading to withdrawal of trimethoprim-sulfamethoxazole were hepatotoxicity (29.4%), gastrointestinal upset (23.5%), and rash (17.6%). Nine patients (26.5%) were switched to echinocandins after failure of trimethoprim-sulfamethoxazole. The median interval before switch from trimethoprim-sulfamethoxazole to echinocandins was 9.0 days (IQR 5.0–14.0). The all-cause and PCP-related in-hospital mortality rate of patients receiving echinocandins as alternative therapy was 20.6% (7/34) and 14.7% (5/34), respectively. The all-cause in-hospital mortality was 0% in mild PCP cases and 29% (7/24) in moderate-to-severe PCP cases. Patients who had failed to respond to first-line trimethoprim-sulfamethoxazole treatment tended to have a higher in-hospital mortality rate than those without first-line trimethoprim-sulfamethoxazole failure (44.4% versus 12.0%, P  = 0.06). Conclusion: Echinocandin therapy might serve as an alternative option for HIV-infected patients with PCP who are intolerable to trimethoprim-sulfamethoxazole. Abstract : Supplemental Digital Content is available in the text